FACTORS AFFECTING UTILIZATION OF ANTENATAL CARE SERVICES IN SANA'A CITY, YEMEN - Seham Othman; Taha Almahbashi; Alabed Ali A. Alabed (Malaysian Journal of Public Health Medicine, 2017)
Antenatal care is a vital part of primary healthcare that is known to improve maternal and newborn outcomes. The aim of this study was to identify the factors affecting utilization of antenatal care services for women in reproductive age in Yemen. This cross-sectional community-based study was conducted in six districts of Sana’a City, Yemen. Data were collected from 460 mothers who gave birth in the past six months via face-to-face interviews at home between September to December 2010. Only 54% of mothers were found to have made four or more antenatal care visits. Almost two third of participants made their first visit during their first trimester due to presence of health problems and did not follow up when they became healthy during pregnancy. Reasons for not receiving antenatal care services due to absence of health problems, high cost of antenatal care services, long waiting time, and poor staff attitude. Sixty percent of participants were unaware of the danger symptoms of common health problems in pregnancy. The significant factors affecting utilization of antenatal services were mother education, residence place, age at first pregnancy, gravida, parity, occurrence of pregnancy without planning, and number of live children (P<0.05). The factors affecting the number of visits were mother education, place of residence, and husband work were (P<0.05). Future healthcare activities should focus on improving women’s awareness of the importance of antenatal care even in the absence of noticeable health problems and lack of education about the common danger signs and symptoms of pregnancy.